Towards The Independence of The Propellant Industry for Munitions and Rocket - Akhmad - Rifai; Era Restu Finalis (JMPM (Jurnal Material dan Proses Manufaktur), 2022)
Indonesia has not yet been able to generate propellants, which are crucial components of the country's defense system. Long-term reliance on imports for ammunition and rocket components can compromise the TNI's operational readiness. These issues and weaknesses include being susceptible to political pressure and having less independence and deterrence factor readiness. Because it affects national pride in national defense, the installation of a propellant factory should not be postponed. Nitrocellulose, the primary raw material of cellulose and nitroglycerin, whose primary raw material is glycerine, is used as the primary raw material in the production of propellants. Domestic industries have generated the two primary raw materials.